The Causes of the Emergence of the Functional Corruption and its Risks - Malkia, Nabil; Bouguerra, Lamria (Journal of Legal Studies and Researches, 2022)
The purpose of this study is to provide an description of the causes of functional corruption emergence and its risks, because there are factors administrative, economic, social and political reasons that will inevitably lead to risks at all levels. The study suggests proposed solutions to eliminate the causes of the functional corruption and then limit or reduce its risks.